The UN at War Peace Operations in a New Era - Karlsrud, John (Springer International Publishing, 2018)
This book is a critical political and institutional reflection on UN peace operations. It provides constructive suggestions as to how the UN and the international system can evolve to remain relevant and tackle the peace and security challenges of the 21st century, without abandoning the principles that the UN was founded upon and on which the legitimacy of UN peace operations rests. The author analyses the evolving politics on UN peace operations of the five veto powers of the UN Security Council, as well as major troop-contributing countries and western powers. He investigates the move towards peace enforcement and counter-terrorism, and what consequences this development may have for the UN. Karlsrud issues a challenge to practitioners and politicians to make sure that the calls for reform are anchored in a desire to improve the lives of people suffering in conflicts on the ground-and not spurred by intra-organizational turf battles or solely the narrow self-interests of member states. Finally, he asks how the UN can adapt its practices to become more field- and people-centered, in line with its core, primary commitments of protecting and serving people in need. "An excellent resource for researchers, policy-makers, practitioners and students, this work provides a very useful analysis on the past, present and future of peace missions, as well as how they have and could face the challenges of today's world." -Séverine Autesserre, Associate Professor, Barnard College,Columbia University, USA "The international community and the new Secretary-General will have a chance to initiate meaningful, transformative reforms in the way the United Nations addresses social, political and security challenges; the road map is provided by John Karlsrud, highly recommended to all international peace and security academics and practitioners." -José Ramos-Horta, Nobel Peace Prize laureate and former President and Prime Minister of Timor Leste "This is the most current, up-to-date assessment of UN Peace Operations available. A must-read for both analysts and practitioners of peacekeeping." -Lise Morjé Howard, Georgetown University, USA .